2004
DOI: 10.1074/jbc.m309481200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Potentiates Cholecystokinin/Gastrin Receptor-mediated Ca2+ Release by Activation of Mitogen-activated Protein Kinases

Abstract: 2؉ ] i in the absence of G17. These data demonstrate that the activation state of the MEK1,2/ERK1,2 pathway can modulate the amplitude of the CCK 2 R-mediated Ca 2؉ release response and identify a novel mechanism for cross-talk between EGF receptor-and CCK 2 Rregulated signaling pathways.The gastrointestinal peptide hormone gastrin-(1-17) (G17) 1 plays an essential role in the regulation of digestion by stimulating gastric acid secretion, histamine synthesis and release, and proliferation of the gastric epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Because EGF exerts its physiologic and pathophysiologic effects through its tyrosine kinase receptor, EGFR/HER-1, by activating multiple signal transduction pathways (16,17,30,55,56), we used several standard approaches to explore whether analogous signaling pathways were involved in the regulation of WISP-2/CCN5 expression by EGF. The studies have shown that EGFR/HER-1 mediates the action of EGF because up-regulation of WISP-2/CCN5 mRNA in MCF-7 cells by EGF could be inhibited by either EGFR-specific siRNA or EGFR-specific tyrosine kinase inhibitor AG30 (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because EGF exerts its physiologic and pathophysiologic effects through its tyrosine kinase receptor, EGFR/HER-1, by activating multiple signal transduction pathways (16,17,30,55,56), we used several standard approaches to explore whether analogous signaling pathways were involved in the regulation of WISP-2/CCN5 expression by EGF. The studies have shown that EGFR/HER-1 mediates the action of EGF because up-regulation of WISP-2/CCN5 mRNA in MCF-7 cells by EGF could be inhibited by either EGFR-specific siRNA or EGFR-specific tyrosine kinase inhibitor AG30 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signal transduction pathways, including Src, Ras, Raf, mitogen-activated protein kinase (MAPK) kinase, c-Jun NH 2 -terminal kinase, and protein kinase C pathways, are involved in EGF-EGFR-induced transcriptional activations of various genes during physiologic and pathophysiologic needs (23,(29)(30)(31)(32). Moreover, estrogen, through its membrane receptor, rapidly activates several downstream signaling cascades that may eventually trigger the cross-talk between ER and EGFR, which in turn leads to activation of several signal transduction pathways and genes required to alter the cell biology of breast cancer (23,33).…”
Section: Involvement Of Signal Transduction Pathways In Egfinduced Wimentioning
confidence: 99%
“…In addition, involvement of MEK1/2 and ERK1/2 pathways has been reported (Olszewska-Pazdrak et al 2004). Thus, with the above considerations and as an extension of earlier works from our group showing an effect of gastrin-17 on NO production, the aim of this study was to investigate in PCAEC the effects of gastrin-17 on [Ca 2C ] c handling and the mechanisms involved.…”
Section: Changes Of Cytosolic Camentioning
confidence: 77%
“…Changes of [Ca 2C ] c have been reported to be also crucial for the response of gastrointestinal cells to CCK receptor agonists. Hence, Ca 2C is an essential signalling molecule in gastrin-17-stimulated cell proliferation (Olszewska-Pazdrak et al 2004) and is involved in gastrin-induced histamine secretion (Shibata et al 2006). In addition, in isolated pig parietal cells, both gastrin-17 and the synthetic peptide pentagastrin increased [Ca 2C ] c in a dose-dependent manner (Cabero et al 1989).…”
Section: Changes Of Cytosolic Camentioning
confidence: 99%
See 1 more Smart Citation